The midpoint P of the line segment joining the points A (-10, 4) and B (-2, 0) lies on the line segment joining the points C (-9, -4) and D (-4, y). Find the ratio in which P divides CD and also, find the value of y.
Answer
Verified
510.9k+ views
Hint: Find the coordinates of the midpoint P of the line segment AB. Then use the section formula of line segment CD for the abscissa of point P to find the ratio in which P divides CD. Use the section formula of line segment CD for the ordinate of point P to find y.
Complete step-by-step answer:
From section formula, if P (x, y) divides the line segment joining \[C({x_3},{y_3})\] and \[D({x_4},{y_4})\] in the ratio m:n, then:
\[x = \dfrac{{m{x_4} + n{x_3}}}{{m + n}};{\text{ }}y = \dfrac{{m{y_4} + n{y_3}}}{{m + n}}{\text{ }}.........{\text{(2)}}\]
Substituting equation (1) in equation (2) and using coordinates of C and D, we get:
\[ - 6 = \dfrac{{m( - 4) + n( - 9)}}{{m + n}}{\text{ }}..........{\text{(3)}}\]
\[ 2 = \dfrac{{m(y) + n( - 4)}}{{m + n}}{\text{ }}...........{\text{(4)}}\]
Simplifying equation (3) to get the ratio in which P divided CD, we get:
\[ - 6 = \dfrac{{ - 4m - 9n}}{{m + n}}{\text{ }}\]
\[ - 6(m + n) = - 4m - 9n\]
\[ - 6m - 6n = - 4m - 9n\]
\[ - 6m + 4m = - 9n + 6n\]
\[ - 2m = - 3n\]
\[\dfrac{m}{n}{\text{ = }}\dfrac{3}{2}{\text{ }}..........{\text{(5)}}\]
Simplifying equation (4) to obtain the value of y, we get:
\[2 = \dfrac{{my - 4n}}{{m + n}}\]
\[2(m + n) = my - 4n\]
\[2m + 2n = my - 4n\]
Gathering terms containing m on RHS and terms containing n on LHS, we get:
\[4n + 2n = my - 2m\]
\[6n = m(y - 2)\]
Divide both sides by n, to get:
\[6 = \dfrac{m}{n}(y - 2)\]
Substituting equation (5) in the above equation, we get:
\[6 = \dfrac{3}{2}(y - 2)\]
Multiply both sides by \[\dfrac{2}{3}\] and simplify.
\[\dfrac{2}{3} \times 6 = y - 2\]
\[4 = y - 2\]
\[y = 6\]
Hence, the value of y is 6
Therefore, P divides CD in the ratio 3:2 and the value of y is 6.
Note: The possibility for mistake is writing the section formula for points \[C({x_3},{y_3})\] and \[D({x_4},{y_4})\] wrongly as \[x = \dfrac{{m{x_3} + n{x_4}}}{{m + n}};{\text{ }}y = \dfrac{{m{y_3} + n{y_4}}}{{m + n}}\] instead of \[x = \dfrac{{m{x_4} + n{x_3}}}{{m + n}};{\text{ }}y = \dfrac{{m{y_4} + n{y_3}}}{{m + n}}\] . You might also think, it is impossible to find three variables from two equations but you are just finding the ratio between m and n and then the value of y, which requires only two equations.
Complete step-by-step answer:
From section formula, if P (x, y) divides the line segment joining \[C({x_3},{y_3})\] and \[D({x_4},{y_4})\] in the ratio m:n, then:
\[x = \dfrac{{m{x_4} + n{x_3}}}{{m + n}};{\text{ }}y = \dfrac{{m{y_4} + n{y_3}}}{{m + n}}{\text{ }}.........{\text{(2)}}\]
Substituting equation (1) in equation (2) and using coordinates of C and D, we get:
\[ - 6 = \dfrac{{m( - 4) + n( - 9)}}{{m + n}}{\text{ }}..........{\text{(3)}}\]
\[ 2 = \dfrac{{m(y) + n( - 4)}}{{m + n}}{\text{ }}...........{\text{(4)}}\]
Simplifying equation (3) to get the ratio in which P divided CD, we get:
\[ - 6 = \dfrac{{ - 4m - 9n}}{{m + n}}{\text{ }}\]
\[ - 6(m + n) = - 4m - 9n\]
\[ - 6m - 6n = - 4m - 9n\]
\[ - 6m + 4m = - 9n + 6n\]
\[ - 2m = - 3n\]
\[\dfrac{m}{n}{\text{ = }}\dfrac{3}{2}{\text{ }}..........{\text{(5)}}\]
Simplifying equation (4) to obtain the value of y, we get:
\[2 = \dfrac{{my - 4n}}{{m + n}}\]
\[2(m + n) = my - 4n\]
\[2m + 2n = my - 4n\]
Gathering terms containing m on RHS and terms containing n on LHS, we get:
\[4n + 2n = my - 2m\]
\[6n = m(y - 2)\]
Divide both sides by n, to get:
\[6 = \dfrac{m}{n}(y - 2)\]
Substituting equation (5) in the above equation, we get:
\[6 = \dfrac{3}{2}(y - 2)\]
Multiply both sides by \[\dfrac{2}{3}\] and simplify.
\[\dfrac{2}{3} \times 6 = y - 2\]
\[4 = y - 2\]
\[y = 6\]
Hence, the value of y is 6
Therefore, P divides CD in the ratio 3:2 and the value of y is 6.
Note: The possibility for mistake is writing the section formula for points \[C({x_3},{y_3})\] and \[D({x_4},{y_4})\] wrongly as \[x = \dfrac{{m{x_3} + n{x_4}}}{{m + n}};{\text{ }}y = \dfrac{{m{y_3} + n{y_4}}}{{m + n}}\] instead of \[x = \dfrac{{m{x_4} + n{x_3}}}{{m + n}};{\text{ }}y = \dfrac{{m{y_4} + n{y_3}}}{{m + n}}\] . You might also think, it is impossible to find three variables from two equations but you are just finding the ratio between m and n and then the value of y, which requires only two equations.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE